2007
DOI: 10.2320/matertrans.48.600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microstructure on the Mechanical Properties and Stress Corrosion Cracking of an Al-Zn-Mg-Sc-Zr Alloy by Various Temper Treatments

Abstract: The high strength Al-Zn-Mg alloy used in the aerospace industry is strengthened by coherent G.P. zones and semicoherent 0 phase. However, this series of aluminum alloys are susceptible to stress corrosion cracking (SCC), particularly when aged to the peak-aged state of T6 temper. In this study, the effect of microstructure on mechanical properties and stress corrosion cracking of the alloy was investigated for alloys tempered to T6, RRA, Two-Step and T7 conditions by tensile test in air, SCC test and polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
(44 reference statements)
2
12
0
Order By: Relevance
“…Also, the sample with a larger precipitate volume fraction tends to have a relatively higher electrical conductivity. This is consistent with that reported in references [20][21][22][23][24][25][26][27]. The evolution for tensile strength of the alloy with the precipitate size suggests a predominant orowan bypassing mechanism for the over-aging states.…”
Section: Saxs Studiessupporting
confidence: 91%
“…Also, the sample with a larger precipitate volume fraction tends to have a relatively higher electrical conductivity. This is consistent with that reported in references [20][21][22][23][24][25][26][27]. The evolution for tensile strength of the alloy with the precipitate size suggests a predominant orowan bypassing mechanism for the over-aging states.…”
Section: Saxs Studiessupporting
confidence: 91%
“…It is reported in several literatures [33][34][35][36] that stress corrosion cracks invariably initiates from the base of the pits and or from the intergranularly corroded/denuded regions. A few literature [37][38][39] has also dealt with investigation of electrochemical behavior and its effect on SCC behavior has been studied many researchers. However, it is very much essential to study the electrochemical behavior of the 7xxx alloys in order to assess its corrosion resistance and also to acquaint with the electrochemical data e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that an increase in the chloride ion content of environment up to 0.6M enhanced the SCC growth rate, and the cracking was slower at higher concentrations. Great efforts have been made to increase the stress corrosion resistance (SCR) of high strength aluminum alloys by optimization of microstructure via heat treatment [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109].…”
Section: Introductionmentioning
confidence: 99%